Detection and threshold-adaptive segmentation of farmland residual plastic film images based on CBAM-DBNet - Xiong, Lijian; Hu, Can; Wang, Xufeng; Wang, Hongbiao; Tang, Xiuying; Wang, Xingwang (International Journal of Agricultural and Biological Engineering, 2024)
Robust, accurate, and fast monitoring of residual plastic film (RPF) pollution in farmlands has great significance. Based on CBAM-DBNet, this study proposed a threshold-adaptive joint framework for identifying the RPF on farmland surfaces and estimating its coverage rate. UAV imaging was used to gather images of the RPF from several locations with various soil backgrounds. RPFs were manually labeled, and the degree of RPF pollution was defined based on the RPF coverage rate. Combining differentiable binarization network (DBNet) with the convolutional block attention module (CBAM), whose feature extraction module was improved. A dynamic adaptive binarization threshold formula was defined for segmenting the RPF’s approximate binary map. Regarding the RPF image detection branch, the CBAM-DBNet exhibited a precision (P) value of 85.81%, a recall (R) value of 82.69%, and an F1-score (F1) value of 84.22%, which was 1.09 percentage points higher than the DBNet in the comprehensive index F1 value. For the RPF image segmentation branch, using CBAM-DBNet to segment the RPF image combined with an adaptive binarization threshold formula. Subsequently, the mean absolute percentage error (MAPE), root mean square error (RMSE), and mean absolute error (MAE) of the prediction of RPF’s coverage rate were 0.276, 0.366, and 0.605, respectively, outperforming the DBNet and the Iterative Threshold method. This study provides a theoretical reference for the further development of evaluation technology for RPF pollution based on UAV imaging. Keywords: binarization threshold adaptive, residual plastic film, object detection, image segmentation, UAV remote sensing DOI: 10.25165/j.ijabe.20241705.8069 Citation: Xiong L J, Hu C, Wang X F, Wang H B, Tang X Y, Wang X W. Detection and threshold-adaptive segmentation of farmland residual plastic film images based on CBAM-DBNet. Int J Agric & Biol Eng, 2024; 17(5): 231-238.